2015
DOI: 10.1002/chem.201503527
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Lactimidomycin and Its Analogues

Abstract: The studies culminating in the total synthesis of the glutarimide-containing eukaryote translation elongation inhibitor lactimidomycin are described. The optimized synthetic route features a Zn(II)-mediated intramolecular Horner-Wadsworth-Emmons (HWE) reaction resulting in a highly stereoselective formation of the strained 12-membered macrolactone of lactimidomycin on a 423 mg scale. The presence of the E,Z-diene functionality was found to be key for effective macrocyclizations as a complete removal of these u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…HMBC correlations between H-3 and C-1/C-1' and the exchangeable NH proton and C-2/C-2' confirmed the presence of a2 ,6 -piperidine- dione,a nd the chemical shift values for this moiety were in good agreement with the literature. [18,19,37,38] Twonetworks of COSY correlations established the structures of the C-2/C-2' to C-6 and C-8 to C-18 regions of the molecule,a nd HMBC correlations further confirmed the locations of the C-8 Me group and the C-9/C-10 double bond. HMBC correlations also showed that C-6 and C-8 are connected via aketo group and that amethyl ketone is attached to C-18.…”
Section: Isolation and Structure Elucidation Of Metabolic Products Ofmentioning
confidence: 81%
“…HMBC correlations between H-3 and C-1/C-1' and the exchangeable NH proton and C-2/C-2' confirmed the presence of a2 ,6 -piperidine- dione,a nd the chemical shift values for this moiety were in good agreement with the literature. [18,19,37,38] Twonetworks of COSY correlations established the structures of the C-2/C-2' to C-6 and C-8 to C-18 regions of the molecule,a nd HMBC correlations further confirmed the locations of the C-8 Me group and the C-9/C-10 double bond. HMBC correlations also showed that C-6 and C-8 are connected via aketo group and that amethyl ketone is attached to C-18.…”
Section: Isolation and Structure Elucidation Of Metabolic Products Ofmentioning
confidence: 81%
“…3-oxo-glycyrrhetinic acid has antitumor activity and expectorant (antitussive) properties 25 . Lactimidomycin has antifungal, antiviral, and anti-cancer properties apart from acting as a direct inhibitor of protein translation inribosomes which is a glutarimide antibiotic derived from the bacterium Streptomyces amphibiosporus 26 . Cardinalins dinalins 4 exhibit anti-cancer properties.…”
Section: Discussionmentioning
confidence: 99%
“…Lactimidomycin (LTM) prevents the ribosome from leaving the start site and blocks the very first round of translation elongation. This recently established anticancer agent [ 15 ] potently inhibits infections of dengue virus and other RNA viruses in cell culture [ 16 ].…”
Section: Introductionmentioning
confidence: 99%